Effect of Mini-invasive Floating Metatarsal Osteotomy on Plantar Pressure in Patients With Diabetic Plantar Metatarsal Head Ulcers. (May 2021) - Tamir, Eran; Tamar, Michael; Ayalon, Moshe; Koren, Shlomit; Shohat, Noam; Finestone, Aharon S.
Background: Distal metatarsal osteotomy has been used to alleviate plantar pressure caused by anatomic deformities. This study's purpose was to examine the effect of minimally invasive floating metatarsal osteotomy on plantar pressure in patients with diabetic metatarsal head ulcers. Methods: We performed a retrospective case series of prospectively collected data on 32 patients with diabetes complicated by plantar metatarsal head ulcers without ischemia. Peak plantar pressure and pressure time integrals were examined using the Tekscan MatScan prior to surgery and 6 months following minimally invasive floating metatarsal osteotomy. Patients were followed for complications for at least 1 year. Results: Peak plantar pressure at the level of the osteotomized metatarsal head decreased from 338.1 to 225.4 kPa ( P < .0001). The pressure time integral decreased from 82.4 to 65.0 kPa·s ( P < .0001). All ulcers healed within a mean of 3.7 ± 4.2 weeks. There was 1 recurrence (under a hypertrophic callus of the osteotomy) during a median follow-up of 18.3 months (range, 12.2-27). Following surgery, adjacent sites showed increased plantar pressure and 4 patients developed transfer lesions (under an adjacent metatarsal head); all were managed successfully. There was 1 serious adverse event related to surgery (operative site infection) that resolved with antibiotics. Conclusion: This study showed that the minimally invasive floating metatarsal osteotomy successfully reduced local plantar pressure and that the method was safe and effective, both in treatment and prevention of recurrence. Level of Evidence: Level III, retrospective case series of prospectively collected data.